2018
DOI: 10.1111/raq.12314
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptides from fish: beyond the fight against pathogens

Abstract: Fish antimicrobial peptides (AMPs) are small peptides whose actions have great implications in the innate immune response of teleost fish, being considered critical as the first line of defence against a wide spectrum of pathogens. Antibiotics have been widely used in aquaculture, resulting in bacterial resistance. The potential of AMPs as alternative to antibiotics makes them a very interesting tool as they represent lower‐risk peptides to develop resistances, or even in the fight against other pathogens such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 226 publications
(327 reference statements)
0
66
0
Order By: Relevance
“…Suggesting that, although charge is an important factor in directing AMP activity, it is not essential. The salmonid AMP with the highest net charge (+30) is Oncorhyncin II, also from rainbow trout [ 15 ]. Although the peptides share antimicrobial efficacy among the select bacterial species, H2A appears to be slightly more effective than Oncorhyncin II against Planococcus citreus , but less effective than Oncorhynchin II against Micrococcus luteus [ 16 ].…”
Section: Structural Properties Of Salmonid Ampsmentioning
confidence: 99%
“…Suggesting that, although charge is an important factor in directing AMP activity, it is not essential. The salmonid AMP with the highest net charge (+30) is Oncorhyncin II, also from rainbow trout [ 15 ]. Although the peptides share antimicrobial efficacy among the select bacterial species, H2A appears to be slightly more effective than Oncorhyncin II against Planococcus citreus , but less effective than Oncorhynchin II against Micrococcus luteus [ 16 ].…”
Section: Structural Properties Of Salmonid Ampsmentioning
confidence: 99%
“…Among the countless biological activities already studied in muscle fish samples, antimicrobial activity is one of the most important, since fish antimicrobial peptides (AMPs) represent ancient host-defense effector molecules [ 6 , 7 ]. In fact, the fish immune system acts as the first line of defense in an aquatic environment, where there is a high level of risk of infection by pathogens, such as bacteria, viruses, parasites and fungi [ 8 ]. Recently, AMPs have been drawing attention as possible substitutes for conventional antibiotics, the resistance to which is continuously increasing [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have already demonstrated that a broad spectrum of AMPs is expressed by fish proteins, including defensins, cathelicidins, hepcidins, histone-derived peptides, and the fish-specific piscidins, which belong to the cecropin family [ 12 ]. It is widely recognized that AMPs are encrypted in parent proteins and they are in their inactive form before protein digestion [ 8 ]. For instance, AMPs can be produced after gastrointestinal digestion [ 13 ] or by the sequential use of proteinases such as pepsin, trypsin, alcalase or pancreatin and even by proteolytic microorganisms or enzymes during fermentation processes [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, peptides from fish showing both antimicrobial and immunomodulatory activities, as well as immunomodulatory peptides from crustaceans, are rich in positively charged and polar amino acids (Figure 4). High percentage of polar and positively charged amino residues in marine organisms can be a consequence of certain specificities of their mechanisms of action, such as interaction with antibodies and complement system, prevention of formation of biofilms, induction of cytokine synthesis, suppression of NO production (Table S2) [105,[128][129][130]. Since the majority of antimicrobial peptides included in this analysis are isolated from fish and bivalves ( Figure 3) this could be an additional factor accounting for a large difference in content of positively charged and polar amino acids among antimicrobial peptides from marine and animal sources.…”
Section: Comparison Of the Structures Of Marine-sourced Peptides Withmentioning
confidence: 99%